PENGARUH ANGGARAN BIAYA OPERASIONAL DAN ANGGARAN PENDAPATAN TERHADAP KINERJA KEUANGAN BERDASARKAN RETURN ON ASSET PADA PDAM TIRTANADI MEDAN - MAJU SIREGAR (LP2MTBM MAKARIOZ, 2021)
The purpose of this study is to find out how the operating cost budget and revenue budget affect financial performancebased on its profitability ratio, namely Return On Asset (ROA) for the period 2016-2018. This research was conducted atTirta Malem Kabanjahe Water District Company starting from February 2019. From the results of the analysis and discussioncan be drawn some conclusions as follows: ROA PDAM Tirta Malem Kabanjahe from 2016 to 2018 experienced fluctuationsand even tends to lose money in 2017 to 2018 a huge influence caused by profit gains that continue to decline until losses.While the total assets each year increase in size. The losses experienced by PDAM every year cause the ROA ratio to besmaller. Which means that the ROA level obtained by the company does not yet have the ability to generate a rate of returnon assets into net profit. The revenue earned by the company fluctuates. With the highest gain occurred in 2016 amountingto Rp.35,994,381,857 where the budget made is smaller than the realization of Rp.7,604,222,500. The company's operatingcosts decreased from the planned so that this year the company still experienced a profit that is not large until the ROAobtained only 0.21.